2014
DOI: 10.3389/fncir.2014.00102
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic modulation of post-synaptic inhibition and locomotor alternating pattern in the spinal cord

Abstract: The central pattern generators (CPGs) for locomotion, located in the lumbar spinal cord, are functional at birth in the rat. Their maturation occurs during the last few days preceding birth, a period during which the first projections from the brainstem start to reach the lumbar enlargement of the spinal cord. Locomotor burst activity in the mature intact spinal cord alternates between flexor and extensor motoneurons through reciprocal inhibition and between left and right sides through commisural inhibitory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 95 publications
(144 reference statements)
4
37
0
Order By: Relevance
“…While this effect has been traditionally tied to a blockade of GABA-dependent neural inhibition, research examining the effect of SCI on spinal levels of KCC2 suggest an alternative interpretation—that administration of bicuculline fosters locomotor behavior because it reduces a GABA-dependent over-excitation that interferes with adaptive plasticity (Grau et al, 2014; Viemari et al, 2011). Here too, descending serotonergic fibers appear to play a key role (Gackiere and Vinay, 2014) and have been shown to impact KCC2 expression and the chloride equilibrium potential (Bos et al, 2013; Gackiere and Vinay, 2014). Our findings fit with an emerging view that suggests alterations in GABA function provide a form of ionic plasticity that regulates the capacity for neural modifications (Ferrini and De Koninck, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While this effect has been traditionally tied to a blockade of GABA-dependent neural inhibition, research examining the effect of SCI on spinal levels of KCC2 suggest an alternative interpretation—that administration of bicuculline fosters locomotor behavior because it reduces a GABA-dependent over-excitation that interferes with adaptive plasticity (Grau et al, 2014; Viemari et al, 2011). Here too, descending serotonergic fibers appear to play a key role (Gackiere and Vinay, 2014) and have been shown to impact KCC2 expression and the chloride equilibrium potential (Bos et al, 2013; Gackiere and Vinay, 2014). Our findings fit with an emerging view that suggests alterations in GABA function provide a form of ionic plasticity that regulates the capacity for neural modifications (Ferrini and De Koninck, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus it would seem to suggest that the application of quipazine would differentially affect these interneurons, resulting in a decrease in the dose needed to evoke coordinated locomotor behavior in adult animals compared to neonates. Another important component of the 5-HT system is that 5-HT 2A seems to facilitate chloride homeostasis following spinal cord injury [36]. Following spinal injury, there is a disruption in chloride homeostasis, resulting in decreased inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, less stimulation is needed to result in activity within neural populations. It has been demonstrated that application of a 5-HT 2A agonist will result in a shift back to pre-injury levels of inhibition [36], which suggests that dose differences among ages do not necessarily arise from disruption in chloride homeostasis. Additionally, following spinal injury there is an up-regulation of 5-HT receptors in the spinal cord [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The serotonergic system modulates both nociceptive and motor spinal cord circuits, 28,31,32,39,45,52,57 and motor activity increases the release of serotonin within spinal and supraspinal areas parallel to reduction of mechanical hyperalgesia. 29,33 Moreover, physical exercise decreases NKCC1 levels and restores KCC2 along with recovery of inhibitory reflex responses in spinal cord injured rats.…”
Section: Possible Role Of Descending Pathwaysmentioning
confidence: 99%